(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
One of the many struggles every growing company faces is choosing the best system to manage its business operations. At first, buying several stand-alone tools may seem cheaper and more effective than purchasing a complete software solution. As a consequence, a company uses several different applications that do not cooperate, making it impossible for employees to work effectively and for the company to prosper. (Drew’s editorial team, July 2022) The development team focused on benefitting hospitals by reducing expenses and delaying work issues. It also helps to give convenience to both patients and staff; Inaccuracy and outdated data will be prevented, and the productivity of hospital workers will increase. The project team proposed a new method in which the Hospital will be using a web-based integration system that aims to help the hospital, especially the core transactions, to manage hospital operations such as Bed and linen management, HOMIS analytics, medical package, and pharmacy. To accomplish these objectives. As a result, the system helps users in their work, such as recording stocks, updating records, viewing real-time analytics, and displaying medical packages. It also enabled nurses, housekeepers, and pharmacists to operate productively and manage patients in a hassle-free manner. Patients can now buy their medical supplies online without going to a physical store. Our project study discussed the core transactions of the Hospital Management System. It is developed through the help of stakeholders to meet the standards of the clients.